Estudo experimental da aplicação de vibração mecânica no processo de manobra de chaves seccionadoras - Setti, Ademilson (2019)
High voltage switches are equipment that allow or block the electricity flow from one point to another. This paper presents an experimental approach, focused on the analysis of mechanical vibration applied in the maneuvering process of the switches. In this study, a maneuvering process was reproduced as it is done in industry, that is, free from vibration; then, the proposal to use mechanical vibration as an alternative aid to increase maneuvering process was tested, using the system proposed by patent BR 10 2013 020198 7. The quantitative parameters analyzed in this study are: vibration frequencies that provides torque relief for opening / closing maneuver, camshaft torque in the maneuvers, bolt torque, mechanical stress and deformation from different parts of the switch structure. In the present work, the obtained data suggests that harmonic mechanical vibration provides technological advances for the disconnecting switch system, such as, the increase of opening and closing maneuvering capabilities. It was also found that mechanical vibration does not affect the structure for the vibration requirements adopted during a survey. Thus, the quality of closure presents positive advances with the use of harmonic mechanical vibration, validating a solution proposed in the patent BR 10 2013 020198 7.